Proton nuclear magnetic resonance and pattern recognition analysis of liver extracts from rats under different anesthetics - Tajima, Tomoyuki (BioMed Central, 2012)
BACKGROUND: Although general anesthesia is widely used in the surgical arena, the mechanisms by which general anesthetics act remain unclear. We previously described alterations in gene expression ratios in hepatic tissue taken from rats treated with anesthetics. Consequently, it is considered that anesthetics influence liver metabolism. Thus, the goal of this study was to use pattern recognition analysis of proton nuclear magnetic resonance spectra to visualize changes in liver metabolic phenotypes in response to widely used intravenous anesthetics (propofol and dexmedetomidine) and inhalational anesthetics (sevoflurane and isoflurane). METHODS: Rats were randomized into 13 groups (n = 6 in each group), and each group received one of following agents: propofol, dexmedetomidine, sevoflurane, isoflurane, or no anesthetic (control group). The liver was directly removed from rats immediately after or 24 h or 48 h after a 6-h period of anesthesia. Hydrophilic compounds were extracted from the liver and were analyzed with proton nuclear magnetic resonance spectroscopy. All spectral data were processed and analyzed by principal component analysis for comparison of metabolite profiles. RESULTS: Data were visualized by plotting principal component (PC) scores. In the plots, each point represents an individual sample. Each group was clustered separately on the plots, and the PC scores of the propofol group were clearly distinct from those of the control group and other anesthetic groups. The difference in PC scores was more pronounced immediately after completion of anesthesia when compared with 24 or 48 h after completion of anesthesia. Although the effect of intravenous anesthetics on the liver dissipated over time, the effect of inhalational anesthetics persisted. CONCLUSIONS: Propofol, dexmedetomidine, sevoflurane and isoflurane exert different effects on liver metabolism. In particular, liver metabolism was markedly altered after exposure to propofol. The effect of anesthesia on the liver under propofol or dexmedetomidine resolved rapidly when compared with the effect under sevoflurane or isoflurane.